Consumer perception and service quality effects on maxim satisfaction: mediating roles of price and value - Maria Helena Chandra; Bernadetha Trisya Devi Soar; Egonius Aldin Raja; Luciano Sergio Taru Dae (International Journal of Enterprise Modelling, 2026)
This study addresses the limited empirical evidence on online transportation service quality in developing regions, focusing on Sikka Regency. While prior studies predominantly focus on metropolitan contexts, little is known about how service quality, price, and perceived value shape customer satisfaction in peripheral regions with distinct socioeconomic characteristics. This study aims to examine the influence of consumer perception, SERVQUAL dimensions, price, and perceived value on customer satisfaction with Maxim services in Sikka Regency. A quantitative approach was employed using survey data from 47 respondents, analyzed through multiple linear regression and sobel test to assess mediation effects. The results indicate that all variables jointly have a significant effect (Sig. 0.000) with high explanatory power (R² = 0.98), although this value should be interpreted cautiously due to the small sample size and potential model overlap. Perceived value (B = 2.341; Sig. 0.000) and price emerge as the most dominant determinants. Notably, the empathy dimension shows a significant negative effect (B = –1.204; Sig. 0.005), suggesting unmet interpersonal expectations. This study contributes by demonstrating context-dependent SERVQUAL effects and emphasizing value-for-money as a key driver of satisfaction in non-metropolitan markets.